PAPAN PENGUMUMAN ONLINE KOMPUTER DAN SISTEM INFORMASI SEKOLAH VOKASI UNIVERSITAS GADJAH MADA - , BUDI WAHYU HERLEN A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, the development of information technology is getting bigger and internet makes information spreads faster and wider. Campusâ notice board is able to support student in daily campus life. Information which is displayed in the notice board, are based on time limit of the notice itself. If the time limit is up, the notices will not be longer exist. Hence, if there is no space for displaying them, the other notices have to wait the notice which is attached in notice board until it disappeared. Therefore, it is needed an information system which can display and spreads the notices of Komputer dan Sistem Informasi (KOMSI) Sekolah Vokasi (SV) Universitas Gadjah Mada (UGM) effectively. The notice board online is implemented using Laravel PHP framework, MySQL as database management. The outputs of this information system provide notices which are well organized by information type, time limit, users, and management notice data. Registered users are classified into 4 levels. There are admin, operator, lecturers/instructor (pengajar) and HIMAKOMSI member (pengurus HIMAKOMSI).